Simulations of long term methane hydrate dissociation by pressure reduction using an extended RetrasoCodeBright simulator - Chejara, Ashok; Kvamme, Bjørn; Vafaei, Mohammad Taghi; Jemai, Khaled (Energy conversion and management, 2013)
► Extended reservoir simulator RetrasoCodeBright into a hydrate simulator. ► Studied methane hydrate dissociation and gas production from it using kinetic approach for hydrate phase transition. ► Compared results from RetrasoCodeBright simulator with the results from other well known hydrate simulators. ► Included geo-mechanical impacts of hydrate dissociation. Methane hydrates in sediments are generally not in thermodynamic equilibrium. This implies that there may be several competing hydrate phase transitions in naturally existing hydrate reservoirs. In addition to dissociation due to instability imposed by changes in temperature and/or pressure which can bring hydrate outside stability also gradients in chemical potential caused by concentration gradients may lead to dissociation or formation of hydrate. Mineral surfaces bring additional thermodynamic phases of impact for hydrate phase transitions. The limited numbers of reservoir simulators which have incorporated hydrate are normally simplified by considering only pressure and temperature as criteria for hydrate stability region. In cases where kinetic description is used it is normally based on oversimplified models, typically models derived from experiments in pressure, temperature volume controlled laboratory cells. In the case of hydrate production through pressure reduction heat transport might dominate the kinetics and simplified heat transport kinetic models are frequently in use for this purpose. In lack of reliable data from full scale hydrate production the reservoir simulators are the only tools which can be used to evaluate efficiency of different production scenarios. Several research groups have been recently working on this subject. The approaches for inclusion of hydrates as a phase, and corresponding production simulation results from different simulators vary. In this work we have applied a fundamentally different approach, in which we have reworked a reactive transport reservoir simulator, namely RetrasoCodeBright into a hydrate simulator. This has been accomplished by adding hydrates as pseudo-mineral components. This opens up for non equilibrium thermodynamic description since kinetic models for different competing hydrate phase transitions can be included through their respective kinetic models. The main theoretical tool for generating these kinetic models has been phase field theory simulations, with thermodynamic properties derived from molecular modeling. The detailed results from these types of simulations provide information on the relative impact of mass transport, heat transport and thermodynamics of the phase transition, which enable qualified simplifications for implementation into RetrasoCodeBright. Details of the simulator, and numerical algorithms, are discussed in detail and some relevant examples are shown. In particular we applied the reservoir simulator to data from Mount Elbert methane hydrate deposits from North Slope, Alaska. Pressure reduction is used as gas production method.